Synthesis of nitrogen-doped KMn₈ O₁₆ with oxygen vacancy for stable zinc-ion batteries - Cui, Guodong (2022)
The development of MnO2 as a cathode for aqueous zinc-ion batteries (AZIBs) is severely limited by the low intrinsic electrical conductivity and unstable crystal structure. Herein, a multifunctional modification strategy is proposed to construct N-doped KMn8 O16 with abundant oxygen vacancy and large specific surface area (named as N-KMO) through a facile one-step hydrothermal approach. The synergetic effects of N-doping, oxygen vacancy, and porous structure in N-KMO can effectively suppress the dissolution of manganese ions, and promote ion diffusion and electron conduction. As a result, the N-KMO cathode exhibits dramatically improved stability and reaction kinetics, superior to the pristine MnO2 and MnO2 with only oxygen vacancy. Remarkably, the N-KMO cathode delivers a high reversible capacity of 262 mAh g-1 after 2500 cycles at 1 A g-1 with a capacity retention of 91%. Simultaneously, the highest specific capacity can reach 298 mAh g-1 at 0.1 A g-1 . Theoretical calculations reveal that the oxygen vacancy and N-doping can improve the electrical conductivity of MnO2 and thus account for the outstanding rate performance. Moreover, ex situ characterizations indicate that the energy storage mechanism of the N-KMO cathode is mainly a H+ and Zn2+ co-insertion/extraction process.